Improved Outcomes and Cost with Palliative Care in the Emergency Department: Case-Control Study - Brandon Chalfin; Spencer M. Salazar; Regina Laico; Susan Hughes; Patrick J. Macmillan (Western Journal of Emergency Medicine)
Introduction: Palliative care consultation teams provide significant advantages for patients, healthcare professionals, and hospitals, particularly in pain management, family support, and clinician satisfaction. Numerous studies show that inpatient palliative care services yield benefits regardless of the timing of initiation, contributing to shortened hospital stays and cost savings. Recent studies have focused on the timing and setting of palliative care, especially in emergency departments (ED), highlighting improved patient outcomes when initiated early. This study explores the potential of embedding hybrid physicians (double-boarded physicians in palliative and emergency medicine) in the ED to further enhance patient care and reduce hospital resources. Methods: This small pilot case-control study included a subset of all patients referred by emergency physicians and hospitalists for palliative care within 24 hours of registration, physically present in the ED. Cases consisted of all the patients seen by hybrid physicians embedded in the ED. Matched controls were seen by palliative care-boarded clinicians (various other primary specialties) during palliative care rounds in the hospital. Matches were based on diagnosis, comorbidities, and referral date. Outcomes measured included hospital length of stay, total charges, discharge disposition, code status changes, and ED visits not resulting in admission. Statistical analyses used chi-square tests for categorical data and Wilcoxon rank-sum test for continuous data. Results: In a four-year period, 68 cases were attended by hybrid physicians over 57 disparate days. These cases had significantly shorter hospital stays (median 2.1 days) compared to controls (6.5 days, P<.001). Total charges were also lower for cases ($37,800) than for controls ($78,000, P<.001). A notable secondary outcome was that 26.5% of ED visits in the case group did not result in hospital admission, compared to all controls being admitted ( P<.001). In addition, more cases than controls had a code status of comfort care at discharge ( P=.07) Conclusion: Embedding hybrid physicians in the ED significantly shortened hospital stays and reduced charges for seriously ill patients. These findings support the further exploration of integrating such physicians into ED settings to enhance patient care and optimize hospital resources.